Assessment on Different Vaccine Formulation Parameters in the Protection against Heterologous Challenge with FMDV in Cattle - Sebastián Di Giacomo; Danilo Bucafusco; Juan Manuel Schammas; Juan Pega; María Cruz Miraglia; Florencia Barrionuevo; Alejandra Victoria Capozzo; Daniel Mariano Perez-Filgueira (Viruses, 2022)
Foot-and-mouth disease (FMD) remains one of the major threats to animal health worldwide. Its causative agent, the FMD virus (FMDV), affects cloven-hoofed animals, including farm animals and wildlife species, inflicting severe damage to the international trade and livestock industry. FMDV antigenic variability remains one of the biggest challenges for vaccine-based control strategies. The current study analyzed the host’s adaptive immune responses in cattle immunized with different vaccine protocols and investigated its associations with the clinical outcome after infection with a heterologous strain of FMDV. The results showed that antigenic payload, multivalency, and revaccination may impact on the clinical outcome after heterologous challenge with FMDV. Protection from the experimental infection was related to qualitative traits of the elicited antibodies, such as avidity, IgG isotype composition, and specificity diversity, modulating and reflecting the vaccine-induced maturation of the humoral response. The correlation analyses of the serum avidity obtained per vaccinated individual might suggest that conventional vaccination can induce high-affinity immunoglobulins against conserved epitopes even within different FMDV serotypes. Cross-reaction among strains by these high-affinity antibodies may support further protection against a heterologous infection with FMDV.